1998
DOI: 10.1111/j.1365-2621.1998.tb15847.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Fish Mince During Multi‐frequency Ohmic Heating

Abstract: A multi-frequency ohmic heating system with 30 Hz~1 MHz range which could deliver 250 watts was developed for measuring electrical conductivity and absolute dielectric loss of food samples. Pacific whiting surimi paste and stabilized mince in the 20~70°C range were tested at frequencies from 55 Hz to 200 kHz. Sample impedance decreased slightly with frequency. The DC electrical conductivity ( dc ) and absolute dielectric loss (⑀Љ) of Pacific whiting surimi paste increased with temperature and salt concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 18 publications
2
13
0
1
Order By: Relevance
“…No corrosion was reported when 5 or 20 KHz was used. The effect of applied frequency confirmed the results of Wu and others (1998) that conducting the experiment at 5 KHz or higher could eliminate product burning and electrode corrosion.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…No corrosion was reported when 5 or 20 KHz was used. The effect of applied frequency confirmed the results of Wu and others (1998) that conducting the experiment at 5 KHz or higher could eliminate product burning and electrode corrosion.…”
Section: Resultssupporting
confidence: 81%
“…Two different (low and high) voltage (V) levels, 60 and 220 V, corresponding to a voltage gradient of 4.3 ± 0.2 and 15.5 ± 0.6 V/cm, respectively, were used for 5 and 20 KHz. However, to minimize electrode corrosion and to prevent heat explosion, which occurs from accumulated current density at the end of the corrosion electrode, only 60 V was used for 55 Hz (Wu and others 1998). …”
Section: Methodsmentioning
confidence: 99%
“…It is predictable because the 50 Hz electrical frequency and stainless steel electrodes were applied in this study. Wu et al (1998) stated that if the electrical frequency lower than 5 kHz was used, the electrolytic corrosion would observably take place at the surface of electrodes made from common food-grade metals. As a consequence of electrode corrosion, some metal ions would migrate into the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Palaniappan and Sastry [2] reported that electrical conductivity is a linear function of temperature, and the relationship can be expressed as: Some research has been done on the electrical conductivity of selected solid and liquid foods, [2,[5][6][7][8] fruit based products, [9][10][11] and meat products. [12][13][14][15] However, relatively little attention has been focused on electrical conductivities of low acid particulate foods.…”
Section: Tulsiyan Sarang and Sastrymentioning
confidence: 99%